Pemberdayaan Masyarakat Melalui Program Sodaqoh Sampah Ekoteologi dan Pertanahan Desa Karangsari Kecamatan Karanganyar - Khusnul Chotimah; Ahmad Syukron Ulinnuha; Dewi Risma Dwi Umayani; Lia Sofiatun Nisa; Iqvinna Camilla Rizky; Arif Rusda Dimaski; Fibiana Aulia Rahma; Irza Aulia Harida; Nur Syifa Azzahro; Aulia Syaifa Putri; Muhammad Faiz Ubaidillah; Selly Yunanda; Wilda Yulia Rusyida (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
The waste problem in Karangsari Village is still an important issue because there is no structured management system and there are still traditional practices such as burning and dumping waste in the open. To answer this challenge, Thematic PKM 63 Group 11 students implemented an ecology-based waste sodaqoh program as a strategy to strengthen environmental awareness based on religious values. This approach interprets waste management as part of human worship and spiritual responsibility as caliphs on earth. This service research uses a qualitative descriptive method with a participatory approach through three stages, namely socialization, education and implementation. Students were directly involved in mapping initial conditions, ecological counseling, assistance in sorting waste, and establishing a waste sodaqoh post as a center for collecting inorganic waste. The results of these activities show a significant increase in community knowledge and participation in waste management. An ecotheological approach makes it easier for people to accept programs, because it is in line with the religious values they believe in. People are starting to get used to sorting waste, reducing burning, and understanding that protecting the environment is part of their faith. This program also encourages the formation of a new culture that integrates religious values and ecological action, so that it has the potential to become a model for sustainable environmental empowerment in other villages.